Strategies to promote public engagement around deprescribing. (November 2018) - Turner, Justin P.; Currie, Janet; Trimble, Johanna; Tannenbaum, Cara
Many seniors remain unaware that certain medications may be harmful, despite high rates of polypharmacy and inappropriate medication use among community-dwelling older adults. Patient education is an effective method for reducing the use of inappropriate medications. Increasing public awareness and engagement is essential for promoting shared decision-making to deprescribe. The Canadian Deprescribing Network was created to address the lack of a systematic pan-Canadian initiative to implement deprescribing among older Canadians. The Canadian Deprescribing Network deliberately included patient advocates in its organization from the outset, in order to ensure a key strategic focus on public awareness and education. In this paper, we present the processes and activities rolled out by the Canadian Deprescribing Network as a blueprint model for engaging the public on deprescribing. Embedded within the structure of the network, the subcommittee on public awareness and engagement implements an action plan that includes needs assessments, population surveys, focus groups, deprescribing fairs, national stakeholders' meetings, public lectures and monthly exchanges with community champions and seniors' organizations. Educational materials and online media have been developed based on the answers to the questions: what information do seniors need about deprescribing? who should this information be delivered to? who needs to deliver the message? and how should seniors be engaged in deprescribing? In conjunction with seniors' organizations, members of the Network have iteratively refined key deprescribing messages, disseminated information about deprescribing, engaged the press and created a grass roots-driven public awareness and education campaign across Canada. Over 3000 seniors and seniors' organizations are involved, with over 25, 000 educational tools being distributed across the country.